Spectroscopic and Thermal Behavior of Na6[(VO)3(P2O7)3]·7H2O - Muglia, Cecilia Isabel (2001)
The electronic (absorption and reflectance) as well as the infrared and Raman spectra of Na6[(VO)3(P2O7)3]·7H2O were recorded and discussed. Its thermal behavior was investigated by means of TG and DTA measurements. After a two-step dehydration, the compound melts at 464°C and, apparently, depolymerization takes place during this process. The characteristics of the pyrolysis residues, collected at different temperatures, were spectroscopically investigated.